CRITICAL THINKING SKILLS FOR LANGUAGE STUDENTS - Patrisius Istiarto Djiwandono (TEFLIN Journal: A publication on the teaching and learning of English, 2013)
Recent developments in language teaching increasingly put a stronger importance on critical thinking skills. While studies in this area have begun to emerge, it is believed that a probe into the learnersâ mind when they process information can contribute significantly to the effort of identifying exactly how our learners think. This study was conducted partly to seek the answers to the issue. A brief training on critical thinking and critical attitude was given to a group of language learners who were studying Business Correspondence. Questionnaires were then used to capture traces of their thinking as they were preparing to accomplish a learning task and while they were listening to their classmatesâ presentation of ideas. The data show the change of their thinking process. After the training there is a tendency from the students to ask more critical questions with slightly higher frequencies. It is concluded then that the brief training has prompted their awareness of critical thinking.Â